MEMORY OWNER: JATIREJO VILLAGE BOUNDARY GATE LUMAJANG DISTRICT - Mawardi Purbo Sanjoyo; Ishak, Ifan Maulana; Dimas Permadi Awwalun. K. R (Journal of Indonesian History, 2025)
This paper is focused on discussing the gate that acts as a monument in building and transforming the collective identity of the community. So that looking at the meaning function of the gate, this paper aims to link the study of the meaning of the gate and the form of memorialization of the history attached to the gate. Like the Jatirejo Village boundary gate, for example, the gate is not only a boundary of power, but also carries a memory that will continue to be carried. The analysis obtained that the Jatirejo village gate displays three important elements, namely First, the symbol of Pancasila and the logo of the Regional Government regarding the cultivation of nationalist patriotism and territorial affirmation as a regional existence. Second, the writing of a Javanese slogan about the values of wisdom in life, so the meaning of Jer Basuki Mawa Beya and the writing Sepi Ing Pamrih Rame Ing Gawe, a Javanese proverb that indirectly teaches Javanese people to work hard without excessive expectations. Third, there are pictures of cassava, rice and corn, which illustrate the local commodities of farmers in Jatirejo Village, where the majority of people work as farmers. Thus, the existence of the gate has walked a long round, from the present to the past and back again, while illustrating the interpedence of various events and historical roles played by the people of Jatirejo Village